Martingale Regressions for a Continuous Time Model of Exchange Rates - Zi-Yi Guo (Global Conference on Business and Finance Proceedings, 2017)
One of the daunting problems in international finance is the weak explanatory power of existing theories of the nominal exchange rates, the so-called “foreign exchange rate determination puzzle”. We propose a continuous-time model to study the impact of order flow on foreign exchange rates. The model is estimated by a newly developed econometric tool based on a time-change sampling from calendar to volatility time. The estimation results indicate that the effect of order flow on exchange rates is more than doubled compared with the traditional econometric estimations. The normality tests of the distribution of regression residuals confirm our application of the new econometric tool.
Keywords: 330